Comporative analysis of banana pseudostems and banana stems as adsorbents for reducing peroxide content and Free Fatty Acids (FFA) in used cooking oil - Fitria, Eliza; Rulen, Betty Nia; Carles, Carles; Nopianto, Nopianto (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
ABSTRACT Background : the increasing production and consumption of palm oil in Indonesia have led to arise in used cooking oil (UCO), classified as hazardous waste due to its high content of free fatty acids (FFA) and peroxides, which are toxic and difficult to degrade. To address this, the use of natural adsorbents such as banana pseudostems and banana stems has gained attention due to their cellulose content, which can effectively absorb harmful compound like FFA and peroxides, improving UCO quality. Method : This experimental study employed a pre-experimental design with a one-group pretest-posttest approach to evaluate the effectiveness of banana pseudostem and banana stem powder, of different mesh size (60, 100, and 200 mesh), in reducing FFA and peroxide levels in UCO. Samples of UCO were obtained from a street food vendor, while the banana plant (Musca acuminata) were collected locally. After immersing the adsorbents in UCO for 72 hour, FFA and peroxide values were analyzed using titration methods. Statistically analysis was performed using a Paired Sample T-Test. Results: The results showed a significant reduction in FFA levels, with the mopst effective reduction observed with 200-mesh adsorbents, where the FFA content decreased from 0.67% to 0.16% for psedostem adsorbent and to 0.20% for stem adsorbents. Peroxide levels were also reduced, with the stem adsorbent reducing peroxide values from 49.60mg/L to 12.92 mg/L, while pseudostem adsorbent reduce it to 14.61 mg/L. Statistical analysis confirmed a significant reduction in FFA (p=0.03), but the reduction in peroxide values was not satistically significant. Conclusion : the particle size of banana pseudostem and banana stem significantly influences the effectiveness of reducing peroxide and FFA levels in UCO. Adsorbents with a particle size of 200 mesh were most effective, with banana pseudostems performing slightly better than banana stems. This study highlight the potential of banana plant material as inexpensive and environmentally friendly adsorbents for UCO management.